CRISPR‐Cas9‐mediated editing of BADH2 gene triggered fragrance revolution in rice. Issue 1 (23rd February 2023) - Imran, Muhammad; Shafiq, Sarfraz; Tang, Xiangru
Abstract: Fragrance is one of the most important quality traits for breeding in rice. The natural aroma substance 2‐acetyl‐1‐pyrroline (2‐AP) is a key fragrance compound among over 200 volatiles identified in fragrant rice. In addition to rice, there are other plant species that contain a germplasm that naturally produces a fragrant aroma. These other plant species all have lower activity levels of the enzyme BETAINE ALDEHYDE DEHYDROGENASE 2 (BADH2). Therefore, improving fragrance efficiency has been a focus of intensive research. Recent studies have engineered BADH2 gene, which is responsible for fragrance trait in non‐fragrant cultivars of rice, using CRISPR‐Cas9. Although engineering rice BADH2 can be useful for upregulating 2‐AP, there are still a lot of restrictions on how it can be applied in practice. In this review article, we discuss the recent developments in BADH2 editing and propose potential future strategies to effectively target BADH2 for transcriptional regulation, with the goal of producing a better fragrance.